Pengembangan Video Tutorial pada Kompetensi Dasar Penerapan Promosi untuk Pemasaran Online Platform Tiktok bagi Siswa SMK Kuliner Fase F (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The rapid development of digital technology has increased the demand for digital marketing competencies among vocational high school students. However, learning activities related to online marketing promotion at SMK Negeri 2 Jombang were still dominated by lecture methods and limited learning media, resulting in low student engagement and practical understanding. This study aimed to develop a video tutorial on the basic competency of implementing promotional strategies for online marketing through the TikTok platform for Culinary Vocational High School students in Phase F, determine its feasibility, and analyze student responses. The study employed a Research and Development (R&D) approach using the 4D model, limited to the Define, Design, and Develop stages. Data were collected through material validation sheets, media validation sheets, and student response questionnaires. The results showed that the developed video tutorial obtained a material expert validation score of 92% and a media expert validation score of 89%, both categorized as very valid. Student responses reached 85% and were categorized as very positive. Therefore, the video tutorial is feasible to be used as an alternative learning medium to improve students’ understanding, learning motivation, and digital promotion skills.